2013
DOI: 10.1093/europace/eut214
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of symptomatic drug-induced long QT syndrome and torsade de pointes in Germany

Abstract: While European annual reporting rates based on spontaneous reports suggest an annual diLQTS/TdP incidence of 0.26 per million in Germany, we estimated a considerably higher incidence of diLQTS/TdP in an active surveillance approach. Further measures are warranted to better sensitize physicians against this potentially life-threatening drug-induced adverse event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(89 citation statements)
references
References 34 publications
2
81
1
5
Order By: Relevance
“…Ostatnio w badaniu przeprowadzonym w Niemczech, w którym zastosowano aktywny nadzór, stwierdzono, że nieskorygowana zapadalność na polekowy LQTS prowadzący do torsade de pointes (TdP) wynosi 3,2/mln osób rocznie [128]. Jeżeli stwierdzi się, że VA może być spowodowana farmakoterapią antyarytmiczną, to podawanie leków mogących działać proarytmicznie należy przerwać, a następnie przeprowadzić odpowiednie kontrolne monitorowanie EKG.…”
Section: Leki Antyarytmiczneunclassified
“…Ostatnio w badaniu przeprowadzonym w Niemczech, w którym zastosowano aktywny nadzór, stwierdzono, że nieskorygowana zapadalność na polekowy LQTS prowadzący do torsade de pointes (TdP) wynosi 3,2/mln osób rocznie [128]. Jeżeli stwierdzi się, że VA może być spowodowana farmakoterapią antyarytmiczną, to podawanie leków mogących działać proarytmicznie należy przerwać, a następnie przeprowadzić odpowiednie kontrolne monitorowanie EKG.…”
Section: Leki Antyarytmiczneunclassified
“…11 A German study estimated the incidence of medication-induced QTc interval prolongation and torsade de pointes together to be 2.5 per million per year for men and 4 per million per year for women. 12 These estimates are drastically higher than the incidence of 0.26 per million figure based on European spontaneous adverse drug reaction reports, 12 implying that the risk of medication-induced prolongation of the QTc interval and torsade de pointes may be much higher than previously believed. Pediatric patients were excluded from these studies; however, there are case reports and reviews [13][14][15] describing cardiac arrest and torsade de pointes in pediatric patients due to several medications.…”
Section: Discussionmentioning
confidence: 91%
“…Several relevant clinical risk factors (such as recent conversion from AF to normal rhythm, bradycardia, hypokalemia, female gender or steroid hormones levels) have been associated with the risk to develop diLQTS or iatrogenic Torsades de pointes [1,12,[27][28][29]. However, individual predictability remains low and it has been suggested that genetic variants might explain a significant proportion of susceptibility to develop diLQTS.…”
Section: Discussionmentioning
confidence: 99%
“…The current understanding favors the additive effect of common and less common genetic variants that reduces the cardiac repolarization reserve [7][8][9][10][11]. As a consequence, diLQTS can develop among individuals with predisposing genetic factors, which favors exaggerated response to a pharmacological challenge with QT-prolonging drugs [1,11] but does not affect cardiac repolarization features at baseline [1,7,12]. Therefore, the detection of patients prone to develop diLQTS ultimately requires prospective evaluation of changes in cardiac repolarization in response to drug therapy.…”
Section: Introductionmentioning
confidence: 99%